Reforma do Ensino Médio e qualidade da educação na Paraíba : indícios, evidências e tendências - Sena, Anne Karoline Cantalice (2025)
This research is part of a context of reforms, driven by the dismissal of President Dilma Vana Rousseff without proof of a crime of responsibility, substantially modifying the macroeconomic political agenda and reverberating in a society project distinct from the three previous governments. In this sense, it is assumed that educational reforms are structuring to contextualize this work, being understood as golden structural changes in educational policy, which concern a conception of education, but, above all, a societal project. Assuming Secondary Education Reform as the theme, the materialization of the policy – standardized in the Base Nacional Comum Curricular (BNCC) for this stage of Basic Education and through changes in the Law of Guidelines and Bases of National Education n. 9,394/1996 via Law no. 13,415/2017 – reflected in state implementation regulations, as is the case with the Proposta Curricular do Estado da Paraíba para o Ensino Médio (PCEP-EM). Through the understanding that the quality of education at PCEP-EM can be associated with total or social, our general objective is to analyze how secondary education reform in Paraíba fits into the context of quality of education. The methodological outlines are based on the description of the Paraíba case, presentation of the epistemological scheme and the definition of the stages and universe of the research. The study considers high school and, specifically, the curricular proposal being implemented, as a case study based on a qualitative approach, documentary analysis and the structuring elements of the “new” high school centered on total and social quality. The results reveal signs, evidence and trends that highlight the instrumentalization of education, precarious teaching working conditions, individual responsibility for school failure, emphasis on student protagonism and the development of social and emotional skills, strengthening of an educational model based on meritocracy, aligning with the logic of total quality.